1999
DOI: 10.1034/j.1600-0420.1999.770607.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diabetic retinopathy using two‐field 60° fundus photography. A comparison between red‐free, black‐and‐white prints and colour transparencies

Abstract: ABSTRACT.Purpose: To assess the severity of diabetic retinopathy and maculopathy by comparing two different photographic methods; two-field 60ae photography using red-free, black-and-white prints and colour transparencies. Methods: Two ophthalmologists independently graded the photographs of 74 patients using grading scales for retinopathy and maculopathy designed for 60ae photography. A set of nine 60ae red-free, black-and-white standard photographs were chosen to represent the severity of principal diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
4
13
1
Order By: Relevance
“…Those early changes are more easily detected by red-free black-on-white photography than on color photographs (34). As the RTA operates with a green heliumneon laser and a black-on-white fundus camera, it meets those requirements.…”
Section: Photographymentioning
confidence: 83%
“…Those early changes are more easily detected by red-free black-on-white photography than on color photographs (34). As the RTA operates with a green heliumneon laser and a black-on-white fundus camera, it meets those requirements.…”
Section: Photographymentioning
confidence: 83%
“…Although ophthalmoscopy provides an effective means of analysing the retina, there is evidence that fundus photographs are more reliable than ophthalmoscopy, for instance, in the diagnosis of diabetic retinal lesions (Harding et al, 1995;von Wendt et al, 1999). Moreover, retinal fundus photography provides the possibility of analysing the produced images in batch mode.…”
Section: Introductionmentioning
confidence: 99%
“…Nonmydriatic fundus cameras allow the acquisition of high-quality digital images with no need for medically induced mydriasis. It has been shown that fundus photographs are more reliable than ophthalmoscopy in the diagnosis of diabetic retinal lesions (21)(22)(23)(24). Therefore, the use of these cameras might be considered for screening, diagnosis, and grading of DR (25)(26)(27).…”
mentioning
confidence: 99%